Role of protease-activated receptor-2 in inflammation, and its possible implications as a putative mediator of periodontitis - Holzhausen, M. [UNESP]; Spolidório, Luis Carlos [UNESP]; Vergnolle, N. (Instituto Oswaldo Cruz, Ministério da Saúde, 2005)
Proteinase-activated receptor-2 (PAR2) belongs to a novel subfamily of G-protein-coupled receptors with seven-transmembrane domains. This receptor is widely distributed throughout the body and seems to be importantly involved in inflammatory processes. PAR2 can be activated by serine proteases such as trypsin, mast cell tryptase, and bacterial proteases, such as gingipain produced by Porphyromonas gingivalis. This review describes the current stage of knowledge of the possible mechanisms that link PAR2 activation with periodontal disease, and proposes future therapeutic strategies to modulate the host response in the treatment of periodontitis.
Keywords: protease; activated receptor-2; alveolar bone loss; inflammation; host response; Porphyromonas gingivalis; periodontitis